IS TRANSLATION IN HIGHER EDUCATION AN ACADEMIC OR VOCATIONAL FIELD? - Wulan Yulian Anggini; Fachri Helmanto (Universitas Indraprasta PGRI, 2023)
Undergraduate higher education in many countries are common to teach translation theories in a class while the students need more practice as close as the professional translator does. The purpose of this study is to explore how undergraduate higher education institution administering the translation class in Indonesia. This study used an exploratory case study method on a translation class of an English Education study program year 2022 with data gathered are from the learning documents, lecturers, and students. The data are analyzed using thematic analysis following steps familiarization, coding, generating, reviewing, defining, naming theme and writing up. The themes are validated using data triangulation that cross checking among the collected data. This study shows that the undergraduate level prepares the academic field of translation that will serve as a base of knowledge to pursue advanced level in the academic and/or goes to specialize for becoming professional translator later. It is recommended to have further study on how to teach the academic field of translation, such as translation teaching model, teaching method, assessment and so on.